Asymmetric synthesis of substituted 1-aminocyclopropane-1-carboxylic acids via diketopiperazine methodology. - Buñuel, E; Bull, S; Davies, S; Garner, A; Savory, E; Smith, A; Vickers, R; Watkin, D (2003)
Diketopiperazinespirocyclopropane 12 is prepared in > 98% d.e. via the conjugate addition of a phosphorus ylide to (6S)-N,N'-bis(p-methoxybenzyl)-3-methylenepiperazine-2,5-dione 2. Deprotection and hydrolysis of adduct 12 and subsequent peptide coupling demonstrate the applicability of this methodology to the asymmetric synthesis of 1-aminocyclopropane-1-carboxylic acids for incorporation into novel peptides. A model for the high level of diastereofacial selectivity observed in the cyclopropanation reaction is presented. A highly selective asymmetric approach (> 98% d.e.) to (S)-[2,2-(2)H2]-1-aminocyclopropane-1-carboxylic acid 29 is also reported via a deuterated sulfur ylide addition to acceptor 2.